PENGEMBANGAN DATABASE PADA WEBSITE SIM-PUL SERIBU - Rr Megy Wulandari Ratna Listi (2021)
Kepulauan Seribu Marine National Park Center is an organization in the field of nature conservation that requires the process of managing data related to conservation activities that have been carried out. Kepulauan Seribu Marine National Park Hall has three offices located in Kepulauan Seribu, with this, often the data or reports of conservation activities are not conveyed properly. Kepulauan Seribu Marine National Park Hall already has a website, but some of the managed data storage is still not running and is well integrated. Therefore, the need for development of the existing database on the website so that the data can be stored and managed properly so that the Thousand Islands Marine National Park Hall can improve business processes. The purpose of this research is to develop a database on the website SIM-Pul Seribu so that the website produces a good and integrated information system. In this development, the author used prototyping as a method of system development.